Адміністративно-правове забезпечення взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності в Україні : автореферат дисертації - Іняхін, В. Є.; Iniakhin, V. Ye. (Харків : Харківський національний університет внутрішніх справ, 2023)
Дисертацію присвячено визначенню сутності та особливостей взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності в Україні. Розкрито методологічні засади такої взаємодії, визначено її поняття та особливості. Окреслено коло принципів та завдань зазначеної взаємодії; надано характеристику її правових засад та встановлено місце серед них адміністративно-правового регулювання. Охарактеризовано адміністративно-правовий механізм взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності в Україні, зокрема виокремлено її напрямки, розкрито рівні та межі, встановлено систему адміністративно-правових форм та методів зазначеної взаємодії. Сформульовано напрями вдосконалення адміністративно-правового забезпечення взаємодії між органами публічного адміністрування та суб’єктами підприємницької діяльності в Україні, у тому числі шляхом використання позитивного зарубіжного досвіду такої взаємодії.

The thesis is devoted to determining the essence and peculiarities of administrative and legal support for interaction between public administration bodies and business entities in Ukraine, and to developing proposals and recommendations aimed at improving administrative legislation in the relevant area. The methodological principles of interaction between public administration bodies and business entities in Ukraine are revealed. The concept and features of interaction between public administration bodies and business entities are defined. The range of principles and tasks of interaction between public administration bodies and business entities is outlined. The author describes the legal basis of interaction between public administration bodies and business entities and establishes the place of administrative and legal regulation among them. The article characterises the administrative and legal mechanism of interaction between public administration bodies and business entities in Ukraine. The directions of interaction between public administration bodies and business entities are determined. The levels and boundaries of interaction between public administration bodies and business entities are revealed. The range of administrative and legal forms and methods of interaction between public administration bodies and business entities is determined. The directions of improvement of administrative and legal support of interaction between public administration bodies and business entities in Ukraine are determined. The foreign experience of interaction between public administration bodies and business entities is summarised and the possibilities of its use in Ukraine are considered. The author also examines the ways to improve the administrative legislation regulating the interaction between public administration bodies and business entities.

Диссертация посвящена определению сущности и особенностей взаимодействия между органами публичного администрирования и субъектами предпринимательской деятельности в Украине. Раскрыты методологические основы такого взаимодействия, определены его понятия и особенности. Обозначен круг принципов и задач указанного взаимодействия; дана характеристика его правовых основ и установлено место среди них административно-правового регулирования. Сформулированы направления усовершенствования административно-правового обеспечение взаимодействия между органами публичного администрирования и субъектами предпринимательской деятельности в Украине, в том числе путем использование положительного зарубежного опыта такого взаимодействия.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Administrative and legal support of interaction between public administration bodies and business entities in Ukraine
Keywords: Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; органи публічного адміністрування; суб’єкти підприємницької діяльності; адміністративно-правове забезпечення; взаємодія; зарубіжний досвід; Україна; адміністративне законодавство; public administration; subjects of entrepreneurial activity; administrative and legal support; interaction; foreign experience; Ukraine; administrative legislation; органы публичного администрирования; субъекты предпринимательской деятельности; административно-правовое обеспечение; взаимодействие; зарубежный опыт; Украина; административное законодательство